2022
DOI: 10.1002/alz.12752
|View full text |Cite
|
Sign up to set email alerts
|

Genome‐wide profiling of circulatory microRNAs associated with cognition and dementia

Abstract: Introduction: MicroRNAs (miRNAs) are post-transcriptional regulators of gene expression. Their role in the pathophysiology of dementia and potential as biomarkers remains undetermined. Methods: We conducted a single-(one-by-one) and multi-marker (joint) analysis to identify well-expressed circulating miRNAs in plasma (total = 591) associated with general cognition and incident dementia, for 1615 participants of the population-based Rotterdam Study.Results: During single-marker analysis, 47 miRNAs were nominall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
2
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 54 publications
1
5
2
1
Order By: Relevance
“…Among the 46 microRNAs associated with cognition in previous population-based studies, miR-340-5p, miR-125b-5p, mir-4732-3p and miR-92a-3p were associated with at least one cognitive score in the same direction in our per microRNA analysis. Of note, miR-4732-3p had been found in two of the previous studies [12,13] and, among these 46 microRNAs, it had the strongest association with cognition in our data. Conversely, seven microRNAs were significantly associated with cognitive scores in the opposite direction in our data, compared to previous studies.…”
Section: Resultssupporting
confidence: 73%
See 3 more Smart Citations
“…Among the 46 microRNAs associated with cognition in previous population-based studies, miR-340-5p, miR-125b-5p, mir-4732-3p and miR-92a-3p were associated with at least one cognitive score in the same direction in our per microRNA analysis. Of note, miR-4732-3p had been found in two of the previous studies [12,13] and, among these 46 microRNAs, it had the strongest association with cognition in our data. Conversely, seven microRNAs were significantly associated with cognitive scores in the opposite direction in our data, compared to previous studies.…”
Section: Resultssupporting
confidence: 73%
“…The first part of our per microRNA analysis consisted of a replication analysis for a priori selected microRNAs. This included 46 microRNAs associated with cognition in previous similar studies [12][13][14][15][16], and 10 microRNAs consistently found to be differentially expressed in the blood of AD and Mild Cognitive Impairment (MCI) patients in a recent meta-analysis [17]. An overview of these studies can be found in Supplementary Table S1.…”
Section: Replication Of Micrornas Previously Associated With Cognitio...mentioning
confidence: 99%
See 2 more Smart Citations
“…Имеющиеся научные данные свидетельствуют о возможности использования miR-92a-3p и miR-532-5p не только в качестве биомаркеров когнитивных функций, но и в контексте изучения молекулярных механизмов заболеваний, сопровождающихся когнитивным снижением [57]. Три микроР-НК оказались общими для когнитивного расстройства и деменции (miR-4539, miR-372-3p и miR-566), а мультимаркерный анализ выявил еще одну общую микроРНК (miR-7106-5p) [58]. Анализ этих четырех общих микроР-НК позволил обнаружить несколько предполагаемых генов-мишеней, экспрессирующихся в головном мозге, и выделить сигнальный путь соответствующей митоген-активированной протеинкиназы.…”
Section: Introductionunclassified